Zoonotic potential of gastrointestinal parasite in long-tailed Macaque Macaca fascicularis at Baluran National Park, Situbondo, East Java, Indonesia - Dyah Ayu Kurniawati; Lucia Tri Suwanti; Nunuk D.R. Lastuti; Setiawan Kusdarto; Endang Suprihati; Mufasirin Mufasirin; Arif Pratiwi (Aceh Journal of Animal Science, 2020)
Baluran National Park (BNP) is one of the highest number of tourist visit among Indonesian national park. In the past decades, excessive feeding has induced change in macaque behaviour which increased the number of recorded human-macaque interaction. The close contact between macaque and humans can increase the risk of disease transmissions. This study aimed to identify gastro intestinal (GI) parasite in the long-tailed macaque. To provide identification, we adopted morphologic methods. We collected 100 faeces from unidentiﬁed individuals of Long-tailed macaque in BNP. Fecal samples were tested using direct smear and modified sugar floatation techniques. Microscopic examination showed 89% (89/100) samples were found to be positive of GI parasite. The prevalence of protozoa infection was higher (89%) than helminth (83%). The most prevalent GI parasite is Trichostrongylus sp (66%) following with  Entamoeba sp. (53%), Strongyloides sp. (32%), Blastocystis sp. (32%), Trichuris sp.(17%), Giardia sp. (10%) and Enterobius sp. (3%). All of GI parasite that successfully identified have zoonotic concern. In conclusion, GI parasites found in faeces of long-tailed macaque at Baluran National Park  potentially a zoonotic transmission.Keywords : GI Parasite; Long tailed Macaque; Baluran National Park; Zoonosis